The relationship between servant leadership and employee retention: the mediating effect of job embeddedness and the moderating effect of organizational culture - Mohgan, K. Kalimuthu (2019)
There is a growing need to meet the demand for information technology (IT) professionals at a time when supply is not only fail to keep pace with the growth in the ICT sector, but also employees are finding many opportunities to move from one job to another. Hence, the main objective of this study is to investigate the relationship between servant leadership, job embeddedness, organizational culture and employee retention in the ICT sector in Malaysia. The study also examined the mediating role of job embeddedness between servant leadership and employee retention, and the moderation effect of organizational culture between servant leadership and job embeddedness. A total of 300 employees across five diverse ICT companies in Kuala Lumpur participated in this quantitative research. Disproportionate stratified random sampling technique and a selfadministered survey method were used to collect the data. Descriptive statistics, correlation and regression analysis were carried out to analyse the data. The findings of this study revealed that servant leadership along with the mediation effect of job embeddedness played critical roles in enhancing IT employees’ retention. However, organizational culture was found to be not moderating the relationship between servant leadership and job embeddedness. Overall, this study attempts to contribute to the body of knowledge by examining the relationships of this study variables which are inadequate. Subsequently, the context of the study being in Malaysia, the findings of the study will contribute to the implications for practicing leaders and policy makers in Malaysia for enhancing IT employees’ retention in order to safeguard the industry. Lastly, the limitations of the study and suggestions for future research are included in this regard.